2019
DOI: 10.1002/jctb.6221
|View full text |Cite
|
Sign up to set email alerts
|

Effective removal of aqueous glyphosate using CuFe2O4@biochar derived from phragmites

Abstract: BACKGROUND: The excess use of glyphosate in both agricultural and nonagricultural areas has led to tremendous health (e.g. cardiac and respiratory impacts) and environmental concerns worldwide. There is an urgent need to find efficient ways to remove glyphosate residue from the aqueous environment. RESULTS: Herein, an effective method for the removal of aqueous glyphosate is developed by employing nano-CuFe 2 O 4 modified biochar (BC) as an adsorbent. The CuFe 2 O 4 @BC adsorbents were prepared through hydroly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Comparing the values obtained using both models, the R 2 values obtained using the pseudo-second-order model are higher than those obtained using the pseudo-first-order model and that the q e exp values agree well with the q e cal values using the pseudo-second-order model (Table ). Both parameters strongly suggest that the adsorption process of Cr­(VI) by five adsorbents follows a pseudo-second-order model at different concentrations, suggesting that the chemisorption process is the rate-limiting step …”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Comparing the values obtained using both models, the R 2 values obtained using the pseudo-second-order model are higher than those obtained using the pseudo-first-order model and that the q e exp values agree well with the q e cal values using the pseudo-second-order model (Table ). Both parameters strongly suggest that the adsorption process of Cr­(VI) by five adsorbents follows a pseudo-second-order model at different concentrations, suggesting that the chemisorption process is the rate-limiting step …”
Section: Resultsmentioning
confidence: 92%
“…Both parameters strongly suggest that the adsorption process of Cr(VI) by five adsorbents follows a pseudo-second-order model at different concentrations, suggesting that the chemisorption process is the rate-limiting step. 55 DFT Calculations. In general, the Fe atom is the most favored adsorption site, consistent with our calculated results, where the major adsorption site was identified as the Fe center.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Furthermore, the chemical modification method can effectively modify biochar surface properties to obtain high adsorption performance. Jia et al (2020) found a higher maximum adsorption capacity of glyphosate of 269 mg.g −1 by nano-CuFe 2 O 4 modified biochar prepared by a coprecipitation method.…”
Section: Adsorptionmentioning
confidence: 89%
“…Adequate evidence exists to support that Fenton system including combination coupling Fenton system (i.e., electro-Fenton, adsorption-Fenton, photo-Fenton processes, and Fenton-like system) is significantly efficient. This is due to shorter contact time and fewer by-products on glyphosate removal under Fenton system [3]. Thus far, the major problem has received attention that it is quite challenging and inconvenient to store and transport liquid hydrogen peroxide (H 2 O 2 ) [4].…”
Section: Introductionmentioning
confidence: 99%